High-precision symbol timing algorithm for specific emitter identification - Yiwei PAN; Hua PENG; Tianyun LI; Wenya WANG (Tongxin xuebao)
The existing symbol timing algorithms have the problems that the method of delay estimation is improper and the calculation precision of the interpolation is insufficient for the pretreatment of specific emitter identification.A high-precision symbol timing algorithm was proposed to solve these problems.Aiming at the former problem,a two-step estimation method was adopted,rough estimation of delay was firstly obtained by the forward algorithm,and then the accurate value was acquired through local search with the demodulated symbols.For the latter problem,a window-based approach was used to design an interpolating filter which could optimize the anti-aliasing characteristics and improve the calculation accuracy.Simulation results show that the proposed algorithm can effectively solve the above problems and achieve better recognition results in the radiation source recognition compared with the conventional symbol timing algorithm.